Computational assessment of upper airway muscular activity in obstructive sleep apnea – In vitro validation. (November 2022) - Ignatiuk, Daniel; Xiao, Qiwei; McConnell, Keith; Fleck, Robert; Schuler, Christine; Schuh, Andreas; Amin, Raouf; Bates, Alister
Abstract: Neuromuscular control of the upper airway contributes to obstructive sleep apnea (OSA). An accurate, non-invasive method to assess neuromuscular function is needed to improve surgical treatment outcomes. Currently, surgical approaches for OSA are based on airway anatomy and are often not curative. When the airway surface moves, the power transferred between air in the airway lumen and the structures of the upper airway may be a measure of airway neuromuscular activity. The aim of this study was to validate power transfer as a measure of externally applied forces, representing neuromuscular activity, through cine computed tomography (CT) imaging and computational fluid dynamics (CFD) analysis in a 3D-printed airway model. A hollow elastic airway model was manufactured. An insufflation/exsufflation device generated airflow within the model lumen. The model was contained in an airtight chamber that could be positively or negatively pressurized to represent muscular forces. These forces were systematically applied to dilate and collapse the model. Cine CT imaging captured airway wall movement during respiratory cycles with and without externally applied forces. Power transfer was calculated from the product of wall movement and internal aerodynamic pressure forces using CFD simulations. Cross-correlation peaks between power transfer and changes in externally applied pressure during exhalation and inhalation were −0.79 and 0.95, respectively. Power transfer calculated via cine CT imaging and CFD was an accurate surrogate measure of externally applied forces representing airway muscular activity. In the future, power transfer may be used in clinical practice to phenotype patients with OSA and select personalized therapies.